Importance of Informal Skills for Sporting Goods Retailers in the Service Relationship - Pichot, Lilian; Pierre, Julien (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
SummaryWe discuss the everyday work of sporting goods salespeople in France, stressing the importance of informal and relational skills in the service relationship, which draws on the seller and buyer’s shared interest in sports. Salespeople do far more than just perform predefined tasks. Their effectiveness depends largely on being able to develop personal relationships with customers.We collected quantitative and qualitative data through four methods: 1) a questionnaire sent in 2019 to all sports and recreational retail managers in the Grand Est region of France (n=61); 2) an analysis of job listings posted in the press, online and in stores in 2019 and 2020 (n=152), which we used to draw up a list of skills and qualifications for the advertised positions; 3) semi-structured interviews with salespeople and store managers (n=20) on their everyday work, their relationships to sporting goods and their perceptions of customer relationships; and 4) ethnographic observation of everyday sales work in ten stores (January-February 2020).In service work, a sense of selflessness is valued, as reflected in the practice of adaptive selling. Salespeople develop a sense of the customers’ lifestyle and approach to sports and create verbal, cognitive and emotional closeness. The personal relationships that develop through such adjustments ultimately facilitate sales transactions, whose meaning is socially constructed by both parties.